SPITTING TYPE SEED DISPERSAL BY DOMESTIC GOAT IN THE ZOOCHORIAL PROCESS OF BLACKTHORN PLUM - Şahin, B.; Kar, S.; Şafak Odabaşı, N. (Annali di Botanica, 2021)
The blackthorn plum, Prunus spinosa L., has fruits with a stony endocarp. It is known that the germination of the Prunus species is long-lasting and challenging. Endozoochory, which is seed dispersal via ingestion by vertebrate animals, has been reported to break the dormancy in many plant species. In this study, a special zoochorial relationship, which was perceived to occur between domestic goats (Capra hircus) and P. spinosa, was investigated with regard to its various aspects. The pits spat by goats during rumination were examined microscopically and compared to the intact pits. The endocarp of pits from goats was seen to be superficially eroded, and the lignified cells were fragmented and broken. The average germination rates were detected in the five experimental groups for the 2018 and 2019 years, respectively, as it follows: 3.85% and 42.3% in the samples from goats with endocarp; 11.4% and 6.8% from goats without endocarp; 2.3% and 59.2% from the tree with endocarp; 3.9% and 9.6% from the tree without endocarp; and 0.8% and 80.0% in the samples sowed as whole dried fruit. A high germination rate and the shortness of the germination period for the first year reveal that the goats, as spitting type seed disperser, play an important supportive zoochorial role for the P. spinosa in nature.